The Influence Of Shape And Angle of Reflection of Flat Mirrors On a Kaleidoscope - Nabila Aprilia; Windi Anggraini; Halimatul Zahra Kurtubi; Amelia Putri Wardhani; Ahmad Suryadi; Fuji Herawati Kusumah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Often, we face difficulties in observing objects in challenging positions. For instance, someone inside a submarine may want to see what lies at the bottom of the sea. One tool based on physics principles that can be employed for this purpose is a kaleidoscope. The formation of images produced by a kaleidoscope can be challenging for those who are unfamiliar with its workings. In a kaleidoscope, multiple reflections occur due to the presence of specific shapes and the number of mirrors used. This research aims to analyze the angles of incident shape and reflected rays in kaleidoscopes with three different shapes, determine the number of images in each kaleidoscope shape, and validate the law of reflection in kaleidoscopes. The process involved using a single object and adjusting the angle, specifically 60Ëš, 90Ëš, and 120Ëš. During the data collection process, it was observed that a 60Ëš angle resulted in 5 images (reflections), a 90Ëš angle resulted in 3 images (reflections), and a 120Ëš angle resulted in 2 images (reflections). The results indicate that as the angle between the mirrors increases, the number of visible or produced images decreases. Conversely, when the distance between flat mirrors is reduced, the number of reflected or produced images increases. The findings on the images in the kaleidoscope are confirmed by the data processing using formulas Â